Report on professional attachment with Singapore Zoological gardens. - Chua, Angela Geok Ching. (2008)
The purpose of this report is to provide a summary of the valuable business training experience that I have gained from working in the Singapore Zoological Gardenes Financial Department, as well as highlighting a few aspects of the training that I found most stimulating.